Objective and Subjective Evaluation of Urban Parks in terms of Outdoor Lighting Conditions: Kosuyolu Yasam Park Example - Kucukkilic Ozcan, Esra; Unver, Fatma Rengin; Aydin, Pinar (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Technically and aesthetically appropriate lighting designs that integrate with the park's appearance and function ensure that park users can easily perceive the environment and feel safe, as well as make more use of these public spaces with the guiding and remarkable effect of the light. In this article, it is aimed to examine the lighting of a park in terms of external lighting criteria with objective and subjective methods. In this context Kosuyolu Yasam Park in the scale of the neighbourhood located in Kosuyolu district of Istanbul has chosen. In the study, firstly the existing lighting conditions of Kosuyolu Yasam Park were determined by using on-site measurements, calculations made in Relux lighting simulation program by means of objective methods and compared with the values given in the standards and evaluated subjectively by conducting surveys. Subsequently, recommendations were made to improve the existing lighting conditions and existing conditions-new suggestions were compared in terms of annual energy use. The objective determinations revealed that the existing lighting arrangement of the park was inadequate in terms of some criteria. In subjective determinations, it was concluded that the users do not have sufficient awareness about unfavorable lighting conditions. In addition, with the recommended lighting designs, it has been proved that the use of luminaires with appropriate technical features not only provide visual comfort conditions but also reduce the energy usage.
Keywords: Outdoor lighting; Kosuyolu Yasam Park; park lighting; Architecture